1993
DOI: 10.1007/bf00185898
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of neonatal denervation on intrafusal muscle fibers in the rat

Abstract: The response of developing muscle spindles to denervation was studied by sectioning the nerve to the medial gastrocnemius muscle of rats at birth. The denervated spindles were examined daily throughout the first postnatal week for changes in ultrastructure and expression of several isoforms of myosin heavy chain (MHC). Each of the three different types of intrafusal muscle fiber exhibited a different response to denervation. Within 5 days after the nerve section nuclear bag2 fibers degenerated completely; nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…However, efferent innervation, as judged by the presence of axons innervating intrafusal fibers towards the poles of spindles, is found in only a fraction of the spindles. Although it is possible that efferent innervation might return at a later time, these results are very similar to those of Kucera et al [1993] in neonatal rat gastrocnemius muscle spindles. They found that afferents reinnervate spindles more readily than gamma motoneurons because either (1) gamma motoneurons were more susceptible to axotomy or (2) gamma motoneurons follow afferents to intrafusal fibers and transient denervation may disrupt this pathway.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, efferent innervation, as judged by the presence of axons innervating intrafusal fibers towards the poles of spindles, is found in only a fraction of the spindles. Although it is possible that efferent innervation might return at a later time, these results are very similar to those of Kucera et al [1993] in neonatal rat gastrocnemius muscle spindles. They found that afferents reinnervate spindles more readily than gamma motoneurons because either (1) gamma motoneurons were more susceptible to axotomy or (2) gamma motoneurons follow afferents to intrafusal fibers and transient denervation may disrupt this pathway.…”
Section: Discussionsupporting
confidence: 63%
“…One week after nerve section, intrafusal fibers in the neonatal rat medial gastrocnemius muscle appear to lose their immunoreactivity to antibody ALD 19 and spindle capsules are degenerated to the point that they cannot be identified by light microscopy [Kucera et al, 1993]. We suggest that a similar effect is found, following phenol block, in muscles from older rats.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The identification of putative gamma motor neurons by molecular markers permitted us to begin to explore the mechanisms that control their specification. Muscle spindle differentiation and maturation is initiated by an inductive signal supplied anterogradely by group Ia proprioceptive afferents to nascent muscle fibers (21,33). In turn, gamma motor neurons depend on trophic support from intrafusal fibers in muscle spindles (34,35).…”
Section: Loss Of Muscle Spindles Leads To Absence Of Putative Gamma Mmentioning
confidence: 99%
“…ALD 19 or ALD 58, antibodies against slow-tonic MHC, are highly specific markers for tracing the fate of nuclear bag intrafusal fibers during development and after denervation at birth (Pedrosa and Tbornell 1990;Kucera and Walro 1993). However, preliminary observations indicated that some denervated extrafusal fibers in neonatal rats also bind mAbs ALD 19 and ALD 58.…”
Section: Introductionmentioning
confidence: 98%